INTEGRASI NILAI-NILAI QUR’ANI DALAM KURIKULUM PENDIDIKAN ISLAM - Masrizal, Masrizal (Hijri, 2022)
Islamic education has the primary mission of shaping individuals who are faithful, knowledgeable, and of noble character. One strategic approach that can be taken is to integrate Qur'anic values into the Islamic education curriculum. This article discusses the urgency, normative basis, and practical strategies for implementing Qur'anic values into the education curriculum. The research method used is library research, involving the analysis of primary and secondary literature related to the Qur'an, hadith, and Islamic education literature. The findings indicate that the integration of Qur'anic values not only strengthens the cognitive aspects of students but also fosters spiritual awareness, social ethics, and moral responsibility in community life.